A Model Study toward the Concise Synthesis of Bromotyrosine‐Derived Spiroisoxazoline Natural Products and Analogous Core Structures. Issue 13 (13th March 2014) - Das, Prasanta; Valente, Edward J.; Hamme, Ashton T.
Abstract: A model study of the first nonaromatic ring based approach toward α‐hydroxyspiroisoxazolines resembling the bromotyrosine‐derived natural product and analogous spiroisoxazoline core structures was implemented. The desired molecular architecture was achieved through the multifunctionalization of a key 1, 3‐diketo spiroisoxazoline. Our strategy could serve as an efficient alternative to previously developed approaches that involve aromatic ring oxidation as the essential step to synthesize this class of natural products. Abstract : The efficient syntheses of functionalized spiroisoxazolines that closely resemble bromotyrosine‐derived spiroisoxazoline natural product core structures are described. This described strategy could serve as an efficient alternative to previously developed approaches that involve aromatic ring oxidation as the essential step to synthesize this class of natural products.